How to deal with morning bad breath: A randomized, crossover clinical trial - Jeronimo M Oliveira-Neto; Sandra Sato; Vinicius Pedrazzi (Wolters Kluwer Medknow Publications, 2013)
Context: The absence of a protocol for the treatment of halitosis has led us to compare mouthrinses with mechanical oral hygiene procedures for treating morning breath by employing a hand-held sulfide monitor. Aims: To compare the efficacy of five modalities of treatment for controlling morning halitosis in subjects with no dental or periodontal disease. Settings and Design: This is a five-period, randomized, crossover clinical trial. Materials and Methods: Twenty volunteers were randomly assigned to the trial. Testing involved the use of a conventional tongue scraper, a tongue scraper joined to the back of a toothbrush's head, two mouthrinses (0.05% cetylpyridinium chloride and 0.12% chlorhexidine digluconate) and a soft-bristled toothbrush and fluoride toothpaste for practicing oral hygiene. Statistical Analysis Used: Data analysis was performed using SPSS version 17 for Windows and NCSS 2007 software (P < 0.05). The products and the periods were compared with each other using the Friedman's test. When significant differences (P < 0.05) were determined, the products and periods were compared in pairs by using the Wilcoxon's test and by adjusting the original significance level (0.05) for multiple comparisons by using the Bonferroni's method. Results: The toothbrush's tongue scraper was able to significantly reduce bad breath for up to 2 h. Chlorhexidine reduced bad breath only at the end of the second hour, an effect that lasted for 3 h. Conclusions: Mechanical tongue cleaning was able to immediately reduce bad breath for a short period, whereas chlorhexidine and mechanical oral hygiene reduced bad breath for longer periods, achieving the best results against morning breath.